Pathomechanisms of TDP‐43 in neurodegeneration. Issue 1 (9th May 2018) - Gao, Ju; Wang, Luwen; Huntley, Mikayla L.; Perry, George; Wang, Xinglong
Abstract : TAR DNA‐binding protein 43 (TDP‐43) proteinopathy is a prominent pathological feature of various major neurodegenerative diseases. In this issue, we first introduce the reader to stages of TDP‐43 proteinopathy during disease progression in amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), and Alzheimer disease (AD), then extensively review our understanding about the potential pathomechanisms underlying TDP‐43 proteinopathy, and finally discuss the possibility of targeting TDP‐43 for the treatment of neurodegenerative diseases. Abstract: Neurodegeneration, a term that refers to the progressive loss of structure and function of neurons, is a feature of many neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD). There is no cure or treatment available that can prevent or reverse neurodegenerative conditions. The causes of neurodegeneration in these diseases remain largely unknown; yet, an extremely small proportion of these devastating diseases are associated with genetic mutations in proteins involved in a wide range of cellular pathways and processes. Over the past decade, it has become increasingly clear that the most notable neurodegenerative diseases, such as ALS, FTLD, and AD, share a common prominent pathological feature known as TAR DNA‐binding protein 43 (TDP‐43) proteinopathy, which is usually characterized by the presence of aberrant phosphorylation, ubiquitination, cleavage and/or nuclear depletion of TDP‐43 in neurons and glial cells. The role of TDP‐43 as a neurotoxicity trigger has been well documented in different in vitro and in vivo experimental models. As such, the investigation of TDP‐43 pathomechanisms in various major neurodegenerative diseases is on the rise. Here, after a discussion of stages of TDP‐43 proteinopathy during disease progression in various major neurodegenerative diseases, we review previous and most recent studies about the potential pathomechanisms with a particular emphasis on ALS, FTLD, and AD, and discuss the possibility of targeting TDP‐43 as a common therapeutic approach to treat neurodegenerative diseases.